PENGARUH PENYULUHAN TERHADAP PENINGKATAN PENGETAHUAN BAHAYA SEKS PRANIKAH PADA REMAJA SISWA SMA N 1 PINANGSORI KECAMATAN PINANGSORI KABUPATEN TAPANULI TENGAH TAHUN 2017 - Dedi Mizwar Tarihoran (JURNAL ILMIAH KOHESI, 2018)
In psychology, a teenager is known as puberty, adolescence, and youth. Adolescence is derived fromLatin, ‘adolescere’ which means growing toward maturity. Psychologically, pre-marriage sex brings about theloss of self-esteem, guilty feeling, feeling of being afraid of being pregnant, lack of moral commitment whichbrings about failure in the post-marriage, and public humiliation. The objective of the research was to find outthe influence of counseling on increasing knowledge of the danger of pre-marriage sex in the students ofSMA N 1 Pinangsori, Pinangsori Subdistrict, Tapanuli Tengah Residence, in 2017.The research used quasi experimental method. The population was230 students, and 70 of them wereused as the samples, The objective of the research was to find out the influence of counseling on increasingknowledge of the danger of pre-marriage sex in the students of SMA N 1 Pinangsori, Pinangsori Subdistrict,Tapanuli Tengah Residence, in 2017.The result of the research showed that there was the increase in knowledge of the danger of premarriagesex from 68.80 to 74 after counseling had been provided, and discussion method had meandifference value of 5.66 so that the most effective method in increasing the students’ knowledge of thedanger of pre-marriage sex at SMA N 1 Pinangsori was discussion method.It is recommended that the management of Puskesmas give information about the danger of premarriagesex to adolescents. The school management should provide health counseling, and UKS shouldincrease the students’ knowledge by using discussion method.